2014
DOI: 10.2188/jea.je20130131
|View full text |Cite
|
Sign up to set email alerts
|

Health-related Quality of Life (HRQOL) Decreases Independently of Chronic Conditions and Geriatric Syndromes in Older Adults With Diabetes: The Fujiwara-kyo Study

Abstract: BackgroundVery few studies have investigated the association between diabetes and impaired health-related quality of life (HRQOL) in older adults, independent of chronic conditions and geriatric syndromes.MethodsWe conducted a self-administered questionnaire survey and structured interviews with 3946 people aged 65 years or older to obtain medical histories of diabetes, chronic conditions, and geriatric syndromes. Blood tests were performed to measure glycated hemoglobin (HbA1c) and plasma glucose levels. HRQO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
2
21
2
1
Order By: Relevance
“…Satoku Nezu and colleagues have shown that health-related quality of life decreases independently of chronic conditions and geriatric symptoms in older adults with diabetes. 27 Thus, we assume that SOURCE Authors' analysis of data from the Barmer and Geisinger surveys. NOTE Scores range from 1 to 5, with 5 representing the greatest congruence with the Chronic Care Model.…”
Section: Discussionmentioning
confidence: 99%
“…Satoku Nezu and colleagues have shown that health-related quality of life decreases independently of chronic conditions and geriatric symptoms in older adults with diabetes. 27 Thus, we assume that SOURCE Authors' analysis of data from the Barmer and Geisinger surveys. NOTE Scores range from 1 to 5, with 5 representing the greatest congruence with the Chronic Care Model.…”
Section: Discussionmentioning
confidence: 99%
“…16 Presence of other diseases accompanying the diabetes makes disease management of diabetic patients difficult 17 and impairs their quality of life. 18,19 Therefore, individuals who have 1 or more chronic conditions need to be supported, accepted, and understood so that they can have a healthy lifestyle, solve their problems, and improve their health-related quality of life. The role of the nurse is important in providing care for patients and responding their individual needs.…”
Section: Burden Of Oads/insulinmentioning
confidence: 99%
“…Previously, it has been known that diabetes patients [1][2][3] as well as hemodialysis (HD) patients [4] experience physical and psychosocial problems. However, very few studies have been performed that investigated which physical and psychosocial problems would be more associated with diabetes patients with nephropathy, and whether these problems would differ between patients with HD and those without HD [5,6].…”
Section: Introductionmentioning
confidence: 99%